إعداد المواد التعليمية لمهارة القراءة في تعليم اللغة العربية لغير الناطقين بها بإندونيسيا ‏ - Nahdliyyatul Azimah (Dirosatuna: Journal of Islamic Studies, 2021)
This study was presented to prepare educational materials as an educational book to develop student's reading skills and experience among second-semester students in Class G, Faculty of Islamic Economics and Commerce, Islamic State University of Sunan Ampel Surabaya.As for the research methodology used, it is developmental research, and the researcher took the research steps presented by Sugiyono. Moreover, the researcher used the pre and post-test and published the questionnaire to the research group to know the effectiveness of the developed book.The results of the research indicated that the educational book "Qirâah Hadidtah" as a companion book for the Intensive Arabic Language Teaching Program at the Islamic State University of Sunan Ampel Surabaya, in addition to that, the educational book is influential in developing students' reading skills as the average score of students at the pre-test is 73% (sound level) And when the post-test is 87% (excellent level). If the "t" test is a calculation greater than a "t" table, the research hypothesis is successful and acceptable. In other words, there is a clear and likely difference between the pre-test and post-test results.